(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The article is devoted to the problems of distance learning, in particular, the use of the "flipped classroom" technology in the educational process. The purpose of the article is to analyze and summarize the experience of using distance learning in the extreme conditions of a pandemic, to show the potential of digital technologies and electronic educational resources created on their basis in teaching the Russian language in a higher educational institution of Kazakhstan. The article discusses the strategy of using the "flipped classroom" technology as one of the forms of blended learning, describes in detail the stages of the educational process, its content and educational and methodological materials on the discipline that make up the learning content. In addition, the article presents the results of a pilot study, the purpose of which was to show that distance learning using the "flipped classroom" technology can be no less effective and successful than full-time education. Summarizing the results of the survey, the authors conclude that over 85% of respondents are satisfied with the results of training using the "flipped class" technology in full or to a greater extent, about 3% are not satisfied with certain parameters of the course. As the unconditional advantages of the “flipped class” model, the authors call the increase in the responsibility of students for their own educational achievements, the development of personal qualities of students, the ability to plan their activities, control them, adjust and improve communicative competencies in all types of speech activity when interacting in the course of working on a joint product. Key words: distance learning, blended learning, flipped classroom technology, learning process, learning content, e-learning resources, learning outcomes.